Assessment of Knowledge and Implementation of AgroEnvironmental Techniques by Farmers in Kanyameshi and Mimbulu Villages, peri-Urban Area of Lubumbashi, HautKatanga Democratic Republic of Congo - Kazadi, Laurent Kabala; Dikoshi, Robert Monga Ilunga; Lokoto, Boniface Mbinga; Mujike, Desire Numbi; Nsele, Maurice Kesonga; Kalumbu, John Tshomba; Fyama, Jules Nkulu Mwine; Mukanya, Moïse Kalambaie Bimn (European Scientific Journal, ESJ, 2025)
Agriculture plays a central role in socioeconomic development, especially in the Democratic Republic of Congo, where it employs about 70% of the population. However, dominant agricultural practices negatively impact the environment, threatening biodiversity and ecosystems. This study aims to promote resilient family farming in the peri-urban area of Lubumbashi, Haut-Katanga. It evaluates farmers’ knowledge and implementation of agro-environmental techniques to mitigate climate change effects. Based on surveys and direct observations of 150 farmers in Kanyameshi and Mimbulu villages, results show that crop association, rotation and manure pits are the most practiced techniques (38%), while agroforestry and biological control are nearly absent. Knowledge of these techniques is closely linked to their perceived impact on climate, environment and agricultural productivity. Although 47% of farmers believe these practices moderately improve farm performance and profitability. The overall awareness remains low. This highlights the need to intensify agro-environmental practices to strengthen family farming resilience.